2013
DOI: 10.1111/dmcn.12281
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the prevalence of severe intellectual disability in children across Europe: feasibility of a common database

Abstract: Aim Our aim was to study the feasibility of creating a framework for monitoring and undertaking collaborative research on intellectual disability at the European level, based on existing databases of children with such disability. Method The characteristics of five existing European intellectual disability databases from four countries (Iceland, Latvia, Ireland, and two in France), were discussed on the basis of ideal criteria set by a working group on childhood intellectual disability as part of the Surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…During the first few years of life only severe impairments can be diagnosed, as mild IDs are only found at school age. A European study showed that the prevalence of severe IDs, defined as an intelligence quotient of less than 50, was 3–5 per 1000 children aged six to eight years . The cumulative prevalence of ID was 0.5% in children at 4.5 years of age in Finland, when aetiological diagnoses were included .…”
Section: Discussionmentioning
confidence: 99%
“…During the first few years of life only severe impairments can be diagnosed, as mild IDs are only found at school age. A European study showed that the prevalence of severe IDs, defined as an intelligence quotient of less than 50, was 3–5 per 1000 children aged six to eight years . The cumulative prevalence of ID was 0.5% in children at 4.5 years of age in Finland, when aetiological diagnoses were included .…”
Section: Discussionmentioning
confidence: 99%
“…It is established that WPPSI–III can be used for older children with intellectual disability. Intellectual disability was classified into mild (IQ 50–70), moderate (IQ 35–50), severe (IQ 20–35), and profound (IQ<20) intellectual disability …”
Section: Methodsmentioning
confidence: 99%
“…Intellectual disability was classified into mild (IQ 50-70), moderate (IQ 35-50), severe (IQ 20-35), and profound (IQ<20) intellectual disability. 33 An adaptive test was performed for all children who had a cognitive test within the study. The Adaptive Behavior Assessment System-II (ABAS-II) was used.…”
Section: Neurodevelopmental Assessmentsmentioning
confidence: 99%
“…The Republic of Ireland is unique in Europe in having a national database of adult persons with intellectual disability in receipt of specialist services or who could benefit from them (van Bakel et al, ). The Irish National Intellectual Disability Database (NIDD) was established in 1995 to ensure that information is available to assist the Department of Health with the planning and provision of appropriate services designed to meet the changing needs of people with intellectual disabilities and their families.…”
Section: National Intellectual Disability Databasementioning
confidence: 99%
“…However, perhaps a major impediment in many countries has been the absence of national systems for documenting the type of services provided and the characteristics of people in receipt of them. Such a system would also allow changes over time to be monitored (van Bakel et al, ). Again, stand alone research projects could not realistically gather such national data, even if all data protection and ethical issues were addressed.…”
Section: Introductionmentioning
confidence: 99%